The Power Of Indonesia’s Liga 1 Digital Broadcast Platform In Influencing And Determining Kickoff Time - Chanif Ainun Naim (FAKULTAS DAKWAH UIN SALATIGA, 2023)
The overnight broadcast schedule of the 2021/2022 Liga Indonesia soccer broadcast has been repeatedly protested by various soccer enthusiasts because it can interfere with the biological clock and mental health of players and supporters. It is suspected that Indosiar and Vidio.com are interfering with PSSI, the national football body, and the league operator. This article examines how Indosiar and Vidio.com as the official broadcasters influence the broadcast by producing, distributing, consuming and rating a program. The digital content analysis answers these questions and helps assess the conclusions of this research which elaborates on digital and platform capitalism. The article finds that the paradigmatic logic underpinning the official broadcaster's commercial strategy is based solely on the collection of digital infrastructure data and the structuring of match viewing hours, rather than an understanding of the interactions of individuals involved in the social realm of soccer matches and television viewers or live streaming.